1998
DOI: 10.2535/ofaj1936.74.6_337
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Nerve Fiber Analysis and Aging Process of the Human Abducent Nerve

Abstract: Summary: Myelinated nerve fibers of the human abducent nerve were analyzed with a new staining method that permits simultaneous observation of the axon and surrounding myelin sheath. The following equipment was employed for the measurements: an image-analyzing digitizer, a microscope equipped with a drawing tube (or camera lucida), and a computer for data storage and statistical analysis. The numbers, transverse areas, and circularity ratios of axons were measured in 10 human abducent nerves. The average numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
4
2
Order By: Relevance
“…The counts in the present study are higher than that reported by Sawabe et al [39] in aged (63-88 years old) subjects, in which the counts ranged from 1473 to 2638. This discrepancy in the findings may be due to the methodological disparity in the two studies, the latter having been done using older morphometric methods using camera lucida drawings and customised programs [39].…”
Section: Myelinated Fibers Countcontrasting
confidence: 84%
See 1 more Smart Citation
“…The counts in the present study are higher than that reported by Sawabe et al [39] in aged (63-88 years old) subjects, in which the counts ranged from 1473 to 2638. This discrepancy in the findings may be due to the methodological disparity in the two studies, the latter having been done using older morphometric methods using camera lucida drawings and customised programs [39].…”
Section: Myelinated Fibers Countcontrasting
confidence: 84%
“…Reports in literature indicate that myelinated fibers predominate in these nerves [7,39]. Our findings ( Table 1 &2) are not quite in agreement with previous studies [33,35] that were on electron microscopic montages, and counting frames were chosen manually, therefore were inherently biased.…”
Section: Myelinated Fibers Countcontrasting
confidence: 49%
“…The methods for fixation, embedding, sectioning, staining and measurement were the same as in our previous reports2, 3,6,7,[9][10][11]14,15). For morphometric measurements, we employed the systemic sampling method.…”
Section: Methodsmentioning
confidence: 99%
“…Myelinated nerve fibers were analyzed in human abducent nerves from 10 cadavers (four males and six females) aged 63–88 (average 74.7) years using the same methods 47 . The average number of fibers was 1997, with a definite decrease with age.…”
Section: Aging Processmentioning
confidence: 99%